Highly efficient thin-film 930 nm VCSEL on PDMS for biomedical applications - Kwon, Ohdo; Moon, Sunghyun; Yun, Yeojun; Nam, Yong hyun; Kim, Nam heon; Kim, Donghwan; Choi, Wonjin; Park, Sungjun; Lee, Jaejin (Scientific Reports, 2023)
Recently, biocompatible optical sources have been surfacing for new-rising biomedical applications, allowing them to be used for multi-purpose technologies such as biological sensing, optogenetic modulation, and phototherapy. Especially, vertical-cavity surface-emitting laser (VCSEL) is in the spotlight as a prospective candidate for optical sources owing to its low-driving current performance, low-cost, and package easiness in accordance with two-dimensional (2D) arrays structure. In this study, we successfully demonstrated the actualization of biocompatible thin-film 930 nm VCSELs transferred onto a Polydimethylsiloxane (PDMS) carrier. The PDMS feature with biocompatibility as well as biostability makes the thin-film VCSELs well-suited for biomedical applications. In order to integrate the conventional VCSEL onto the PDMS carrier, we utilized a double-transfer technique that transferred the thin-film VCSELs onto foreign substrates twice, enabling it to maintain the p-on-n polarity of the conventional VCSEL. Additionally, we employed a surface modification-assisted bonding (SMB) using an oxygen plasma in conjunction with silane treatment when bonding the PDMS carrier with the substrate-removed conventional VCSELs. The threshold current and maximum output power of the fabricated 930 nm thin-film VCSELs are 1.08 mA and 7.52 mW at an injection current of 13.9 mA, respectively.
Keywords: Automobile Driving; Dimethylpolysiloxanes; Excipients; Lasers; Phototherapy